2021
DOI: 10.1155/2021/5542534
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Tunisian General Practitioners in the Management of Patients at Risk of Infective Endocarditis: A Cross-Sectional Study

Abstract: Objectives. This work aimed to estimate the knowledge and practice of general dentists in the governorate of Manouba regarding the management of patients at risk of infective endocarditis. Materials and Methods. A survey involving private sector general dentists in the governorate of Manouba was performed. It contained 21 questions, and it was addressed to 111 dentists. Only 82 dentists responded. To carry out the descriptive study, we used the SPSS software version 21.0. Results. Our results proved the lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The finding that some dentists do not agree on whether to or not to prescribe prophylactic antibiotics in high-risk patients confirms a recent finding by [ 28 ] who concluded that antibiotic prescribing practices were inconsistent, and dentists' practices did not meet the highest antibiotic stewardship standards. Furthermore, findings from this study highlight the lack of consensus in the guidelines and perhaps the confusion surrounding this area as suggested by [ 29 ] and Lagha et al [ 30 ]. This further suggests that the majority of Jordanian dentists follow the European [ 22 ] and American guidelines [ 24 ].…”
Section: Discussionmentioning
confidence: 58%
“…The finding that some dentists do not agree on whether to or not to prescribe prophylactic antibiotics in high-risk patients confirms a recent finding by [ 28 ] who concluded that antibiotic prescribing practices were inconsistent, and dentists' practices did not meet the highest antibiotic stewardship standards. Furthermore, findings from this study highlight the lack of consensus in the guidelines and perhaps the confusion surrounding this area as suggested by [ 29 ] and Lagha et al [ 30 ]. This further suggests that the majority of Jordanian dentists follow the European [ 22 ] and American guidelines [ 24 ].…”
Section: Discussionmentioning
confidence: 58%
“…Initially, 1085 studies were identified (Figure I), from which 33 studies were selected after screening the titles and abstracts. Eleven studies were excluded: in five of them (KOKOMOTO et al, 2018;LAGHA et al, 2021;MAYBODI et al, 2018;NAKANO AND OOSHIMA, 2011;RYALAT et al, 2016), AHA data could not be isolated; five (BROOKS, 1980;KUNZEL AND SADOWSKY, 1989;NELSON AND BLARICUM, 1989;SADOWSKY et al, 1985;SADOWSKY AND KUNZEL, 1988) did not measure in detail the variables included in this systematic review and one (ROCHA et al, 2008) did not specify which guideline was followed.…”
Section: Resultsmentioning
confidence: 99%